GENDER AND EMPLOYEE PARTICIPATION IN DECISION MAKING (PDM) - Mohamed Shaed, Maslina Binti; Ishak, Suraiya Binti (Journal of Technology Management and Business, 2015)
In today’s organizations, employee participation in decision making (PDM) is become as one of the important issue around the world. Although the term has been widely used in research, studies on employee PDM especially from gender perspectives are limited. Even the number of people joining the workforce continuing to increase, the issues on gender PDM is growing and become a major area of concern worldwide. The topic on gender equality between men and women in PDM is a crucial issue and need a better understanding. Previous studies indicated that gender diversity and balance number of women and men in PDM can lead to positive outcomes in the organization. Therefore, the main objective of the study is to review the literature on gender and employee PDM especially in Malaysia context. This is a conceptual paper and based on secondary sources of data from past literatures and Department of Statistics Malaysia. The review of this study hopes to give some contributions of knowledge on gender and PDM among employees and give a better understanding on the issue of employee’s PDM in organizations.